A review of likelihood ratios in forensic science based on a critique of Stiffelman "No longer the Gold standard: Probabilistic genotyping is changing the nature of DNA evidence in criminal trials". (May 2020) - Buckleton, John; Robertson, Bernard; Curran, James; Berger, Charles; Taylor, Duncan; Bright, Jo-Anne; Hicks, Tacha; Gittelson, Simone; Evett, Ian; Pugh, Simone; Jackson, Graham; Kelly, Hannah; et al.
Highlights: Recent criticism reprises some objections to the use of LR s in forensic science. We find that LR s do not infringe the ultimate issue. LR s do not change the beyond reasonable doubt standard. LR s do not infringe the presumption of innocence. Propositions should be exhaustive in the context of the case. Abstract: Stiffelman [1] gives a broad critique of the application of likelihood ratios ( LR s) in forensic science, in particular their use in probabilistic genotyping (PG) software. These are discussed in this review. LR s do not infringe on the ultimate issue. The Bayesian paradigm clearly separates the role of the scientist from that of the decision makers and distances the scientist from comment on the ultimate and subsidiary issues. LR s do not affect the reasonable doubt standard. Fact finders must still make decisions based on all the evidence and they must do this considering all evidence, not just that given probabilistically. LR s do not infringe on the presumption of innocence. The presumption of innocence does not equate with a prior probability of zero but simply that the person of interest (POI) is no more likely than anyone else to be the donor. Propositions need to be exhaustive within the context of the case. That is, propositions deemed relevant by either defense or prosecution which are not fanciful must not be omitted from consideration.